2018
DOI: 10.1002/mc.22791
|View full text |Cite
|
Sign up to set email alerts
|

Abrus agglutinin stimulates BMP‐2‐dependent differentiation through autophagic degradation of β‐catenin in colon cancer stem cells

Abstract: Eradicating cancer stem cells (CSCs) in colorectal cancer (CRC) through differentiation therapy is a promising approach for cancer treatment. Our retrospective tumor-specimen analysis elucidated alteration in the expression of bone morphogenetic protein 2 (BMP-2) and β-catenin during the colon cancer progression, indicating that their possible intervention through "forced differentiation" in colon cancer remission. We reveal that Abrus agglutinin (AGG) induces the colon CSCs differentiation, and enhances sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 48 publications
1
21
0
Order By: Relevance
“…Cyclin D1, one of the major cell-cycle mediator proteins, is overexpressed in the cancer cells due to the increased β-catenin levels. Thus, there is a crucial role of β-catenin, a component of the Wnt signaling pathway, in activating the genes for growth regulation involving cellular survival, proliferation and metastasis [105][106][107][108][109]. It was shown that rhein induced cell-cycle arrest at the G0/G1 and S phases in A549 lung cancer cells and BEL-7402 hepatocellular cancer cells, respectively [54,110].…”
Section: Wnt Signaling Pathwaymentioning
confidence: 99%
“…Cyclin D1, one of the major cell-cycle mediator proteins, is overexpressed in the cancer cells due to the increased β-catenin levels. Thus, there is a crucial role of β-catenin, a component of the Wnt signaling pathway, in activating the genes for growth regulation involving cellular survival, proliferation and metastasis [105][106][107][108][109]. It was shown that rhein induced cell-cycle arrest at the G0/G1 and S phases in A549 lung cancer cells and BEL-7402 hepatocellular cancer cells, respectively [54,110].…”
Section: Wnt Signaling Pathwaymentioning
confidence: 99%
“…Wnt/β-catenin signaling, which is the key mediator for the progression of malignancies [56], also plays a critical role in the development and metastasis of HCC cells [57,58]. Accumulating evidence suggests that the activation of the Wnt/β-catenin pathway could play a key role in HCC [59].…”
Section: Pathways Controlled By Lncrnas In Hcc Metastasismentioning
confidence: 99%
“…In a recent study, we found that AGG‐induced autophagy in cervical cancer cells following endoplasmic stress by inhibiting the Akt/PH domain (Panda et al, ), and triggered PUMA‐induced selective mitochondrial elimination in glioblastoma cells to initiate apoptosis through ceramide generation (Panda, Naik, Meher, et al, ). In addition, AGG‐induced autophagy‐mediated differentiation in colon cancer stem cells (Panda, Naik, Praharaj, et al, ), resulting in a significant antitumor effect. However, the potential role of AGG in inducing senescence, as well as the underlying mechanism, is unclear.…”
Section: Introductionmentioning
confidence: 99%